2017
DOI: 10.1038/ncomms16046
|View full text |Cite
|
Sign up to set email alerts
|

Deeply divergent archaic mitochondrial genome provides lower time boundary for African gene flow into Neanderthals

Abstract: Ancient DNA is revealing new insights into the genetic relationship between Pleistocene hominins and modern humans. Nuclear DNA indicated Neanderthals as a sister group of Denisovans after diverging from modern humans. However, the closer affinity of the Neanderthal mitochondrial DNA (mtDNA) to modern humans than Denisovans has recently been suggested as the result of gene flow from an African source into Neanderthals before 100,000 years ago. Here we report the complete mtDNA of an archaic femur from the Hohl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
134
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(166 citation statements)
references
References 53 publications
21
134
0
11
Order By: Relevance
“…For example, a Siberian Neanderthal has AMH genes introgressed c. 110 kya [7], and an early AMH with Neanderthal anatomical features c. 40 kya from Romania [8] had Neanderthal ancestry just 4-6 generations before [9]. Recent data suggests that while Neanderthals and Denisovans clearly form a clade, the mtDNA groups the former with AMH due to their original mtDNA being replaced by an AMH-like lineage probably through interbreeding before c. 270 kya [10]. It is now clear that such interbreeding did leave traces in contemporary modern humans outside Africa at the level of a few percent of the genome, with regional and inter-individual variation probably due to repeated interbreeding with Neanderthals and Denisovans [5 ,11 ,12 ].…”
Section: The Human Treementioning
confidence: 99%
See 1 more Smart Citation
“…For example, a Siberian Neanderthal has AMH genes introgressed c. 110 kya [7], and an early AMH with Neanderthal anatomical features c. 40 kya from Romania [8] had Neanderthal ancestry just 4-6 generations before [9]. Recent data suggests that while Neanderthals and Denisovans clearly form a clade, the mtDNA groups the former with AMH due to their original mtDNA being replaced by an AMH-like lineage probably through interbreeding before c. 270 kya [10]. It is now clear that such interbreeding did leave traces in contemporary modern humans outside Africa at the level of a few percent of the genome, with regional and inter-individual variation probably due to repeated interbreeding with Neanderthals and Denisovans [5 ,11 ,12 ].…”
Section: The Human Treementioning
confidence: 99%
“…1: 2.5-5.8% Denisova genome from archaic hominin having diverged 0.9-1.4 mya [16]; 2: mtDNA introgressed c. 270 kya into a Neanderthal (Hohlenstein-Stadel, Germany) from an African lineage leading or related to AMH [10] (see also [4]); 3: at least 0.5% genome coming from a Neanderthal population closer related to the Atai Neanderthals [16]; 4: 1.0-7.1% gene flow from AMH into Altai Neanderthals [7] (see also [9]); 5,6,8,9: multiple introgressions from Neanderthals into various modern human populations outside Africa resulting in about 2% (regionally and inter-individually variable, slightly more in East Asia) Neanderthal DNA [5 ,11 ,12 ]; 7: Denisova introgression resulting in about 2-4% Denisovan DNA in Melanesia (less in e.g. South Asia [5 ,12 ]).…”
Section: Functional Genetic Differences Between Amh and Neanderthalsmentioning
confidence: 99%
“…Once in the region, humans probably encountered and interbred with Neanderthals. As evidence, he points to a 2017 ancient-DNA study that suggested interbreeding had occurred before 200,000 years ago 8 .…”
Section: Close Encountersmentioning
confidence: 99%
“…HT metody dovolují vytvářet také "úplné" knihovny a-RNA a a-mt-DNA. S takovými DNA a RNA knihovnami lze porovná-vat genom pravěkých a současných populací a také hledat u současných populací genetické příměsi -admixtures -které například ukazují křížení pravě-kých populací, jejich rozšíření a migrační cesty (Posth et al 2017). HT metody třetí generace umožnují také analýzu několik set tisíc let staré a-DNA, i když toto je doslova na hranicích možností současné genetiky a bioinformatiky.…”
Section: Nové Metodologie -Zásadní Pokrok V Paleogeneticeunclassified
“…Možná kolonizovali i další oblasti jako Papuu Novou Giuneu a případně i Austrálii. Analýza genomu evropského archaického člověka pak ukazuje, že genom neandrtálců, ne nezbytně neandrtál-ci jako takoví, se začal formovat už před 700 tisíci lety a k oddělení genomu (čili fylogenetických linií) neandrtálců od původního archaického Homo sapiens došlo přibližně před 550 až 750 tisíci lety (Posth et al 2017 (Mayer et al 2016).…”
Section: B I O L O G I E C H E M I E Z E M ě P I Sunclassified